An Unusual Case of Infantile Spasms Due to a Pathogenic Variant in the MECP2 Gene - Charkhand, Behshad; Liu, Natarie; Barrett, Karlene T.; Al-Hertani, Walla; Scantlebury, Morris H. (Journal of Pediatric Neurology, 2020)
The infantile spasms (IS) syndrome is a developmental epileptic encephalopathy disorder characterized by epileptic spasms occurring in infancy, hypsarrhythmia on the electroencephalography (EEG) and developmental arrest or regression. The etiologies include structural, metabolic, and genetic causes. We report an unusual case of IS due to a de novo variant in the MECP2 gene. The patient also had variants of uncertain significance in the SCN9A and SCN5A genes inherited from the father and mother, respectively. This report highlights the need for broad genetic testing in MECP2-related disorders with atypical presentations to better understand the disease etiology.
Keywords: epileptic encephalopathy; Rett's syndrome; cardiomyopathy